Ischaemum agharkarii (Andropogoneae, Poaceae), a new species from Northern Western Ghats, India - Gorade, Purushottam; Datar, Mandar N.; Choudhary, Ritesh Kumar; Pathare, Prajakta S. (Phytotaxa, 2016)
Ischaemum agharkarii, a new species of Poaceae from the Northern Western Ghats of India is described and illustrated here. It is closely similar to two Indian endemic species, I. travancorense and I. santapaui but differs in having hairy first node, presence of side nodules on lower glume of both sessile and pedicelled spikelets, band of hairs on ventral side of lower glume and other morphological features. We provide detailed morphological description, distribution map and photographs of the new species.